The Contribution of Entrepreneurial Competency and Principal's Leadership on the Learning School and Its Implication on Teachers' Innovative Performance - Ariyani, Dwi; Suyatno, Suyatno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The study aimed to examine the influence of entrepreneurial competency and the principal's leadership on the learning school and its implication on the teachers' innovative performance. The study belongs to quantitative research using a cross-sectional design with ninety teachers as the samples. The analysis concluded several findings. First, entrepreneurial competency reached the beta score of 0.107, showing that it has no significant influence on learning school. Second, the managerial competency has a positive impact on the learning school, which was as much as 0.644. Third, entrepreneurial competency reached the beta score of 0.022, indicating that it has no significant influence on the teachers' innovative performance. Fourth, similarly, managerial competency reached a score of 0.005, showing that it does not influence the teachers' innovative performance. Fifth, learning school negatively influences the teachers' innovative performance, with a score of -0.355, showing its significant effect. Sixth, entrepreneurial competency through learning school positively influences the teachers' innovative performance, with a score of 0.059. And seventh, managerial competency through learning school positively affects the teachers' innovative performance, with a score of 0.233. The research implies a relative influence of the principal's entrepreneurial and managerial competencies on developing the learning environment and the teachers' innovative performance at school.